Reposisi Qanun Desa Berbasis Kearifan Lokal Dalam Upaya Penegakan Syariat Islam di Tingkat Gampong/Desa - Muhammad Rusdi Bin Muhammaddiah Muhammad Ihsan (Prodi Tata Negara (Siyasah) IAIN Langsa, 2019)
This research is an attempt to understand and explain the repositioning of qanun based local wisdom in the effort of enforcing Islamic law at the village. In the context of Acehnese society (after the implementation of Islamic Sharia rules), at the village has not accommodated the implementation of Islamic law such as the establishment of village qanun in the areas of worship, syiar and adat gampong. Qanun gampong should be an extension of Acehnese qanun atprovincial, district/city level based on local wisdom of community/gampong community. Therefore, this study is an effort to re-functioning local qanun based on local wisdom which is not contradictory to higher qanun province, regency/municipality qanun where village qanun will be able to balance the implementation of Islamic law between qanun syariat Islam in Aceh with village qanun. Interest to review this concept, especially as an effort to raise the spirit of Islam at the village level. On the other hand, it is also interesting to see how the track record of the implementation of Islamic Shari'a in the gampong level. This research is descriptive, with approach of Shari'ah discipline and cultural anthropology. Techniques of collecting data through Library Research (literature review), and Indepth interviews with informants are capable with this study. The results of this study indicate that the village apparatus is still hesitant in forming the Islamic Shari'ah qanun because it is absent at the district level, so one of the efforts to restore the village qanun position which previously had not existed was to integrate the value of local wisdom in qanun, in addition to not be separated from the Islam law